(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
Glucose syrup is a product of starch hydrolysis that is widely used in the food industry and other industrial sectors. Currently, the production of glucose syrup is predominantly carried out through enzymatic processes due to their higher efficiency and environmental friendliness. Amylase enzymes play a crucial role in converting starch into simple sugars. This study aims to describe the role of amylase enzymes at each stage of glucose syrup production based on a literature review. The research method employed is descriptive research using a literature study approach, involving data collection from scientific journals, books, and other relevant literature sources. The data were qualitatively analyzed by examining the function of amylase enzymes during the liquefaction and saccharification stages. The results of the review indicate that α-amylase plays a role in the liquefaction stage by breaking down starch into dextrins, while glucoamylase functions in the saccharification stage by converting dextrins into glucose. The use of amylase enzymes can enhance process efficiency and produce glucose syrup with a higher glucose content. Therefore, amylase enzymes play an essential role in determining the success of enzymatic glucose syrup production.